Hubungan Kepatuhan Diet dengan Kadar Glukosa Darah Sewaktu pada Pasien Diabetes Melitus Tipe 2 (DMT2) di Rumah Sakit Bhayangkara H.S. Samsoeri Mertojoso Surabaya - Keysha Berlian Santoso; Cleonara Yanuar Dini; Wildan Alfira Gusrianto; Aulia Putri Srie Wardani (PT Bukuloka Literasi Bangsa, 2026)
Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disease characterized by hyperglycemia resulting from insulin resistance and impaired insulin secretion. One of the main pillars of its management is dietary therapy based on the 3J principles, namely appropriate amount, type, and meal schedule. This study aimed to analyze the relationship between dietary adherence based on the glycemic index, glycemic load, and meal schedule and random blood glucose levels among hospitalized patients with T2DM at Bhayangkara H.S. Samsoeri Mertojoso Hospital, Surabaya. This observational analytic study used a cross-sectional design and involved 85 patients selected through total sampling. Glycemic index and glycemic load data were obtained using the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), meal schedule data were collected through interviews, and random blood glucose data were obtained from medical records upon admission to the Emergency Department. Data were analyzed using Spearman’s rho and Pearson correlation tests with α = 0.05. A total of 89.4% of respondents adhered to the selection of low-glycemic-index carbohydrates, 56.5% had a high glycemic load, 74.1% did not adhere to meal schedules, and 75.3% experienced hyperglycemia. Glycemic index was not associated with random blood glucose levels (p = 0.184), whereas glycemic load (r = 0.383; p < 0.001) and adherence to meal schedules (r = −0.558; p < 0.001) were significantly associated. In conclusion, glycemic load and adherence to meal schedules were associated with random blood glucose levels, whereas glycemic index was not. Keywords: type 2 diabetes mellitus; glycemic index; glycemic load; meal schedule; random blood glucose